Association of TERT Promoter Mutation 1,295,228 C>T With BRAF V600E Mutation, Older Patient Age, and Distant Metastasis in Anaplastic Thyroid Cancer - Shi, Xiaoguang (J Clin Endocrinol Metab, 2015)
CONTEXT: The aggressive role of TERT promoter mutations has been well established in differentiated thyroid cancer but has not been established in anaplastic thyroid cancer (ATC). RESEARCH DESIGN: We tested the mutation status by sequencing genomic tumor DNA and examined its relationship with clinicopathological characteristics of ATC. RESULTS: Among 106 American and Chinese ATC samples, TERT 1,295,228 C>T (termed TERT C228T) mutation was found in 37 (34.9%) cases, TERT promoter mutation 1,295,250 C>T was found in four cases (3.8%), and the two mutations were mutually exclusive and collectively found in 41 cases (38.7%). TERT C228T occurred in 28 of 90 (31.1%) wild-type BRAF cases vs nine of 16 (56.3%) BRAF V600E cases, with an odds ratio of 2.85 (95% confidence interval, 0.96–8.42; P = .05). Patient age was 67.6 ± 13.6 vs 61.6 ± 11.4 years in the TERT C228T vs wild-type TERT patients (P = .02), demonstrating an association between TERT C228T and older patient age. This association was also seen within the American cohort. In this cohort, which had more available clinicopathological data, TERT C228T was associated with distant metastasis of the tumor; specifically, distant metastasis occurred in 15 of 18 (83.3%) TERT C228T patients vs eight of 26 (30.8%) wild-type TERT patients, with an odds ratio of 11.25 (95% confidence interval, 2.53–50.08; P = .001). No association was found with patient sex, tumor size, lymph node metastasis, and extrathyroidal invasion of ATC. CONCLUSIONS: This is the largest study on the aggressive role of TERT promoter mutations in ATC, demonstrating an association of TERT C228T with BRAF V600E, older patient age, and tumor distant metastasis in ATC.